HuguR : website for screening students’ mental health at Reykjavík University - Bjarki Már Friðriksson 1998-; Ingólfur Orri Gústafsson 1999-; Natalia Potamianou 1994-; Patrekur Ingi Sigfússon 2000- (2022)
The entrance to the university marks a new era for a young adult. Throughout their studies, students face new challenges, trying to adjust to the academic demands, leave their houses, be more independent and interact with a more diverse range of new people. In addition, for the past two and a half years, students around the world had to face another challenge; COVID-19 and a global pandemic. In most countries it was followed by a lockdown where most universities had to close their doors and move all the classes online which many students faced difficulties to engage effectively. The social distancing and the restrictions also limited the students’ opportunities to meet new people and socialize. All these challenges affect the wellbeing and mental health of university students which has been a concern even before COVID-19 pandemic. Digitalization efforts across a variety of sectors have been proven to be a successful way of lowering costs while increasing the quality of service significantly. In addition, digital support for mental wellbeing is particularly useful for young people since it is established that they seek online help resources to support their mental health even before COVID-19. Young people aged 18-25 also make use of digital tools due to their increased accessibility and privacy. Online resources can be free and not everyone is in the position to pay for therapy-counseling. Another research supports that a digital platform functions as a bridge between patients and healthcare professionals. HuguR is Reykjavik University’s website for supporting students' mental health and well-being. The goal of the project is to design and develop HuguR to screen students’ mental health with standardized questionnaires and feedback tailored for students that will suggest methods to improve or support the students' mental health. The website also contains a self-help tools section where students can get immediate feedback about the most common negative feelings. If the students want to participate in the ...